2004
DOI: 10.1038/sj.bjc.6602080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gemcitabine on APE/ref-1 endonuclease activity in pancreatic cancer cells, and the therapeutic potential of antisense oligonucleotides

Abstract: Apurinic/apyrimidinic endonuclease (APE) is a key enzyme involved in DNA base excision repair (BER) that is often expressed at elevated levels in human cancers. Pancreatic cancer cells treated with the nucleoside analogue gemcitabine (2 0 , 2 0 -difluoro-2 0 deoxycytidine) showed increases in APE/redox effector factor (ref-1) protein levels (approximately two-fold for Panc-1 and six-fold for MiaPaCa-2), with corresponding increases in endonuclease activity. These results suggested that the activation of APE/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 20 publications
5
64
0
Order By: Relevance
“…Our results are supported by those of others in that the suppression of APE1 results in hypersensitivity to chemotherapeutic agents (10,26,27). Additionally, targeted reduction of Ape1/Ref-1 protein by specific anti-sense oligonucleotides renders mammalian cells hypersensitive to methylmethane sulfonate (MMS), H 2 O 2 , bleomycin, temozolomide (TMZ) and gemcitabine (22,28,29). Moreover, Robertson and colleagues found that elevated expression of APE1 in testicular cancer cell lines results in resistance to certain therapeutic agents, such as bleomycin and radiation (21).…”
Section: Cell Cycle Perturbations Aftersupporting
confidence: 88%
“…Our results are supported by those of others in that the suppression of APE1 results in hypersensitivity to chemotherapeutic agents (10,26,27). Additionally, targeted reduction of Ape1/Ref-1 protein by specific anti-sense oligonucleotides renders mammalian cells hypersensitive to methylmethane sulfonate (MMS), H 2 O 2 , bleomycin, temozolomide (TMZ) and gemcitabine (22,28,29). Moreover, Robertson and colleagues found that elevated expression of APE1 in testicular cancer cell lines results in resistance to certain therapeutic agents, such as bleomycin and radiation (21).…”
Section: Cell Cycle Perturbations Aftersupporting
confidence: 88%
“…From a clinical perspective, APE1 overexpression has been observed in numerous cancer types (37). Additionally, reduced expression of APE1 using RNA interference has been shown to sensitize cells to treatment by numerous therapeutic agents (38)(39)(40)(41). Small molecules that inhibit the AP endonuclease activity of APE1 could thus be extremely valuable in combination therapies for treating cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple labs, including our own, have reported that the PANC-1 cell line is more chemoresistant than other cell lines, often exhibiting higher IC 50 values. [24][25][26][27][28][29] In this study, we also demonstrate that D-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (PDMP), a glucosylceramide synthase inhibitor and gemcitabine, a nucleoside analog, enhance the antitumor activity of Lip-C 6 . We show that the biological effect of Lip-C 6 is achieved through inhibition of Akt phosphorylation, and suggest that the distinctive action of the anti-metabolite gemcitabine can be used to prime the PANC-1 cells to the action of Lip-C 6 .…”
Section: Introductionmentioning
confidence: 92%